1991
DOI: 10.1073/pnas.88.14.6214
|View full text |Cite
|
Sign up to set email alerts
|

Genes encoding receptors for insulin and insulin-like growth factor I are expressed in Xenopus oocytes and embryos.

Abstract: Insulin and insulin-like growth factor I (IGF-I) initiate their metabolic, growth, and differentiation effects through binding to the insulin receptor and the IGF-I receptor, two members of the tyrosine kinase family of receptors. To study the role of these peptides and receptors in early development, we used the polymerase chain reaction and embryo-derived RNA to generate partial cDNA sequences of the insulin receptor and IGF-I receptor from the amphibian Xenopus laevis. Three unique tyrosine kinase-related s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(34 citation statements)
references
References 35 publications
3
31
0
Order By: Relevance
“…This analysis demonstrated that, in tsA-201 cells under basal conditions, the activity of endogenous TKs was dominated by the action of PTPs. When measured 48 h after transfection, Kir2.1 cDNA gave rise to inwardly rectifying I Kir2.1 currents with large amplitudes that averaged 1.97 Ϯ 1.12 nA (n ϭ 10) measured in the patch-clamp-whole cell configuration at Ϫ120 mV and in elevated (25 Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…This analysis demonstrated that, in tsA-201 cells under basal conditions, the activity of endogenous TKs was dominated by the action of PTPs. When measured 48 h after transfection, Kir2.1 cDNA gave rise to inwardly rectifying I Kir2.1 currents with large amplitudes that averaged 1.97 Ϯ 1.12 nA (n ϭ 10) measured in the patch-clamp-whole cell configuration at Ϫ120 mV and in elevated (25 Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…The mobilities of a set of prestained protein markers (in thousands) are indicated. Although Xenopus oocytes resume meiosis in response to either insulin or IGF-1, circumstantial evidence has suggested that an endogenous IGF-1 receptor mediates this response (6,27). Recent evidence has indicated that mammalian IRS-1 is a major substrate for the IGF-1 receptor as well as the insulin receptor and hence may mediate the cellular response to IGF-1 (20,33).…”
Section: Vol 15 1995 Molecular Cloning Of a Xenopus Irs-1-like Cdnamentioning
confidence: 99%
“…However, at the end of neurulation and during organogenesis IR is also restricted to ectodermal and mesodermal tissues, such as optic vesicles, brain, otic vesicles, branchial arches, somites, and pronephros. IGF-1R transcripts can be detected at all stages of embryogenesis (Scavo et al, 1991;Zhu et al, 1998). However, IR and IGF-1R differ in posttranscriptional regulation as binding assays suggest a biphasic pattern of expression: IGF-1R is expressed at high levels in the oocyte and during embryogenesis, whereas the expression level of IR is higher in tadpole stages.…”
Section: Identification Of Embryonic X Laevis Irs-1 a Gene Expressementioning
confidence: 92%